RANCANG BANGUN SISTEM INFORMASI RESERVASI STUDI KASUS PADA QUEEN TOUR BERBASIS WEB - Ari Kusuma Irawan; Didik Kurniawan; Ossy Dwi Endah Wulansari (Jurnal Pepadun, 2021)
Agents travel agents are now more and more developing, the very rapid information technology has provided new examples in all fields of human activity that will change their habits in carrying out its activities. Queen Tour engaged in the field of tourism trying to utilize technology to expand the distribution and market reach with the intention of increasing sales of tour packages offered. In the reservation service travel packages, data management at Queen Tour used for this is still done manually. In making a reservation, consumers must call in advance to confirm the date and time of travel to the Queen Tour. Then information system of Queen Tour reservation was created using the laravel framework. This system is intended for prospective customers to see the contents of existing travel packages. The system includes a reservation menu, gallery and feedback. And there is an automatic recording of data reporting by the system making it easier for admin work. This information system has been tested black-box with the acquisition of an average test value of 95.77%.